Martin's physical pharmacy and pharmaceutical sciences : physical chemical and biopharmaceutical principles in the pharmaceutical sciences - Sinko, Patrick J. PhD, RPh, Professor II (Distinguished), Parke-Davis Chair Professor in Pharmaceutics and Drug Delivery Ernest Mario School of Pharmacy, Rutgers, The State University of New Jersey, Piscataway, New Jersey. (Lippincott, 2017)
Martin's Physical Pharmacy and Pharmaceutical Sciences is considered the most comprehensive text available on the physical, chemical, and biological principles that underlie pharmacology. This 7th Edition puts a stronger focus on the most essential, practical knowledge, and is updated to reflect the broadening scope and diversity of the pharmaceutical sciences.